The Influence of Integrity, Work Discipline, and Competence Through Work Motivation on the Performance of BPJS Ketenagakerjaan Malang City Employeesenagakerjaan Malang City Employees - Ranuaji, Muhammad (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This quantitative research aims to analyze the influence of Integrity (X1), Work Discipline (X2), and Competence (X3) on Employee Performance (Y) with Work Motivation (Z) as a mediating variable at BPJS Ketenagakerjaan (Social Security Agency) Malang City. Background Problems: The research examines the necessity of improving Employee Performance, which is characterized by operational challenges such as delayed claim resolution and low response speed. Novelty: The novelty lies in testing the mediating role of Work Motivation in simultaneously integrating the three dimensions (Integrity, Discipline, and Competence) within a public service environment that is highly sensitive to both ethics and efficiency. Research Methods:The research used a saturated sample of 28 employees, representing the total population. Data were analyzed using the Structural Equation Modeling – Partial Least Square (SEM-PLS) method via SmartPLS 4.0 software. Finding/Results:The evaluation model showed excellent predictive power (Q2 = 0.89) with valid and reliable indicators. Integrity, Work Discipline, and Competence each had a positive and significant effect on both Work Motivation and Employee Performance (P-Value < 0.05). Work Motivation was proven to be a significant partial mediator in all three relationships, meaning the direct effects of the exogenous variables are reinforced through motivation. Conclusion: It is concluded that Work Motivation serves as a significant partial mediating variable. The key implication is that strategies to improve employee ethics (integrity, discipline) and expertise (competence) must be accompanied by initiatives to enhance work motivation to effectively boost performance.